Osteomalacia - Khan, Muhammad Ali; Shah, S. Musanif; Rehman, Masood ur; Saeedi, Muhammad Ilyas; Kumar, Mohan (Journal of Postgraduate Medical Institute, 2011)
Introduction Osteomalacia and rickets result from defective mineralization of bone which is usually caused by insufficiency of vitamin "D". Osteo-malacia refers to clinical consequences of defective mineralization of the organic matrix of adult skeleton. The term rickets is reserved for the same pathology in growing skeleton. It is mostly caused by vit. "D" insufficiency, however defective mineralization can also be due to resistance to vit. "D" , hereditary hypophosphatemia, hypophosphatasia and certain renal tubular disorders. Major dietary sources of vitamin "D". Are fortified foods, fish oils and dairy products. Poor diet, Multiple pregancies and lactation are the main causes of osteomalacia in our patients.Common presenting features are bone pains and deformities of the skeletal system. Every year our unit diagnose on an average 3 cases of Osteomalacia. Typically the patients is a multiparous female, with poor dietary hisoty. Occasional cases of malabsorption and chronic renal failure causing osteomalacia are also noted. In this paper we report a young unmarried girl with osteomalacia due to poor diet.